Lysosomal enzyme binding to the cation-independent mannose 6-phosphate receptor is regulated allosterically by insulin-like growth factor 2 - Richard N. Bohnsack; Sandeep K. Misra; Jianfang Liu; Mayumi Ishihara-Aoki; Michaela Pereckas; Kazuhiro Aoki; Gang Ren; Joshua S. Sharp; Nancy M. Dahms (Scientific Reports)
Abstract The cation-independent mannose 6-phosphate receptor (CI-MPR) is clinically significant in the treatment of patients with lysosomal storage diseases because it functions in the biogenesis of lysosomes by transporting mannose 6-phosphate (M6P)-containing lysosomal enzymes to endosomal compartments. CI-MPR is multifunctional and modulates embryonic growth and fetal size by downregulating circulating levels of the peptide hormone insulin-like growth factor 2 (IGF2). The extracellular region of CI-MPR comprises 15 homologous domains with binding sites for M6P-containing ligands located in domains 3, 5, 9, and 15, whereas IGF2 interacts with residues in domain 11. How a particular ligand affects the receptor’s conformation or its ability to bind other ligands remains poorly understood. To address these questions, we purified a soluble form of the receptor from newborn calf serum, carried out glycoproteomics to define the N-glycans at its 19 potential glycosylation sites, probed its ability to bind lysosomal enzymes in the presence and absence of IGF2 using surface plasmon resonance, and assessed its conformation in the presence and absence of IGF2 by negative-staining electron microscopy and hydroxyl radical protein footprinting studies. Together, our findings support the hypothesis that IGF2 acts as an allosteric inhibitor of lysosomal enzyme binding by inducing global conformational changes of CI-MPR.